Examining the intersection of cognitive and physical function measures: Results from the brain networks and mobility (B-NET) study - Thompson, Atalie C.; Miller, Michael E.; Handing, Elizabeth P.; Chen, Haiying; Hugenschmidt, Christina E.; Laurienti, Paul J.; Kritchevsky, Stephen B. (Frontiers in Aging Neuroscience, 2023)
Background and Objectives: Although evidence exists that measures of mobility and cognition are correlated, it is not known to what extent they overlap, especially across various domains. This study aims to investigate the intersection of 18 different objective cognitive and physical function measures from a sample of unimpaired adults aged 70 years and older. Research Design and Methods: Canonical correlation analysis was utilized to explore the joint cross-sectional relationship between 13 cognitive and 6 physical function measures in the baseline visit of the Brain Networks and Mobility Function (B-NET) Study (n=192). Results: Mean age of participants was 76.4 years. Two synthetic functions were identified. Function 1 explained 26.3% of the shared variability between the cognition and physical function variables, whereas Function 2 explained 19.5%. Function 1 termed “cognitive and physical speed” related the extended Short Physical Performance Battery (eSPPB), 400m walk speed, and Dual Task gait speed measures of physical function to semantic fluency animals scores, Digit Symbol Coding (DSC), and Trail Making Test B. Function 2 termed “complex motor tasks and cognitive tasks” related the Force Plate Postural Sway Foam Task and Dual Task to the following cognitive variables: MoCA Adjusted Score, Verbal Fluency L words, Craft story immediate and delayed recall, and Trail Making Test B. Discussion and Implications: We identified groups of cognitive and physical functional abilities that were linked in cross-sectional analyses, which may suggest shared underlying neural network pathway(s) related to speed (Function 1) or complexity (Function 2). Translational Significance: Whether such neural processes decline before measurable functional losses or may be important targets for future interventions that aim to prevent disability also remains to be determined.